"Elaboración de chocolate de siete cruces internacionales de cacao (Theobroma cacao L.) seleccionados en la finca experimental la Represa" - Tigselema Zambrano, Solanyi Marley (2018)
The objective of this research is to elaborate chocolate from seven interclonal crosses of cocoa (Theobroma cacao L.) selected in the Experimental Farm "La Represa", belongs to Universidad Técnica Estatal de Quevedo (UTEQ). A completely randomized design (DCA) with seven treatments and three repetitions was used. The statistical analysis was carried out using the ANOVA variance analysis and the means were compared through the Tukey test (P≤0.05), The chemical properties (fat, acidity and energy), the organoleptic properties (generalities, basic flavors, specific flavors, defects) were evaluated using a descriptive test to the dark chocolate that was tasted by a panel constituted by 10 semi-trained judges, and an economic analysis was carried out showing variability in the treatments due to the formulations used. With the following treatments: T1 (DICYT-H 258), T2 (DICYT-H 259), T3 (DICYT-H 262), T4 (DICYT-H 263), T5 (DICYT-H 264), T6 (DICYT-H 267), T7 (CCN-51 Control). For the fat variable, the best treatment was DICYT-H 258 (37.83), for the variable acidity the lowest value was obtained by the CCN-51 (2.04) statistically different from the DICYT-H 259 (8.79), for energy there was no statistical significance, a general average of 607 was obtained. For the organoleptic variables, the DICYT-H 262 obtained a floral profile (Arriba Flavor). For the economic analysis no benefit was found because the raw material was not purchased, however the highest cost was for the CCN-51 treatment with 51.20 USD, the lowest cost was the DICYT-H 258 with 40.20 USD. Keywords: cocoa, interclonal crosses, chemical and organoleptic quality